2017
DOI: 10.1515/cclm-2016-0756
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated miR-16 expression is an independent indicator of relapse and poor overall survival of colorectal adenocarcinoma patients

Abstract: Overexpression of the cancer-associated miR-16 predicts poor DFS and OS of colorectal adenocarcinoma patients, independently of clinicopathological factors that are currently used for prognostic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…In contrast, miR-16 was upregulated in CT and S, particularly in the LOW grade and no-Met patients, suggesting that high level of miR-16 in cancer tissues is an early diagnostic marker of CRC. This is consistent with several studies that have reported high levels of miR-16 in CRC tissues [60] and/or its association with overall survival [61,62], but in contrast to other studies that have reported its downregulation in CRC [63]. Because this miRNA was downregulated in all CSC types, its reduced expression in patients with CRC could be a marker of poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, miR-16 was upregulated in CT and S, particularly in the LOW grade and no-Met patients, suggesting that high level of miR-16 in cancer tissues is an early diagnostic marker of CRC. This is consistent with several studies that have reported high levels of miR-16 in CRC tissues [60] and/or its association with overall survival [61,62], but in contrast to other studies that have reported its downregulation in CRC [63]. Because this miRNA was downregulated in all CSC types, its reduced expression in patients with CRC could be a marker of poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…Among the evaluated studies, 49 demonstrated the downregulation of miR-199b 47, 48 , miR-6852 106 , miR-302c 67 , miR-466 68 , miR-650 123 , miR-196b-5p 70 , miR-944 71 , miR-30d 72 , miR-296 73 , miR-187 124 , let-7a-5p 98 , miR-132 99 , miR-206 100 , miR-148a 125 , miR-33b 76 , miR-99b-5p 120 , miR-154 78 , miR-217 126 , miR-149 79 , miR-194 80 , miR-7 56 , miR-24-3p 54 , miR-29b 127 , miR-15a 34 , miR-16 34, 36 , miR-204-5p 128 , miR-96-5p 121 , miR-193a-5p 108 , miR-100 81 , miR-133a 41 , miR-139-5p 129 , miR-124-5p 130 , miR-335 82 , miR-378 101 , miR-126 40 , miR-378a-3p 58 , miR-378a-5p 58 , miR-218 83 , miR-138 110 , miR-625 111 , miR-212 112 , miR-124 131 , miR-22 49 , miR-133b 39 , miR-193a-3p 104 , miR-195 113 and miR-30c 103 associated with worse prognosis (lower overall survival) of CRC patients. Fifty-six studies identified the upregulation of miR-181a 3133 , miR-182 43, 44 , miR-1296 84 , miR-888 64 , miR-28-5p 132 , miR-183 45, 46 , miR-200c 114 , miR-34a 133 , miR-15a-5p 134 , miR-181c 135 , miR-24-3p 53 , miR-16 35 , miR-7 55 , miR-96 86 , miR-1260b 115 , miR-20a-5p 63 , miR-517a 87 , miR-503 136 , miR-106b 88 , miR-211 137 , miR-320e 89 , miR-592 90 , miR-196a 57 , miR-196b 57 , miR-376a …”
Section: Resultsmentioning
confidence: 99%
“…In total, 17 studies demonstrated the downregulation of 18 miRs associated with worse disease free-survival such as miR-196b-5p 70 , miR-944 71 , miR-30d 72 , miR-22 50 , miR-296 73 , miR-199b 47 , miR-187 124 , let-7a-5p 98 , miR-132 99 , miR-29b 127 , miR-15a 34 , miR-16 34 , miR-34a-5p 65 , miR-193a-5p 108 , miR-138 110 , miR-126 8 , miR-212 112 and miR-124 131 . Twenty-one studies associated the upregulation of miR-888 64 , miR-28-5p 132 , miR-183 45 , miR-200c 114 , miR-34a 133 , miR-15a-5p 134 , miR-181c 135 , miR-24-3p 53 , miR-16 35 , miR-96 86 , miR-1260b 115 , miR-20a-5p 63 , miR-517a 87 , miR-503 136 , miR-106b 88 , miR-320e 89 , miR-196a 57 , miR-196b 57 , miR-224 51 , miR-494 61 , miR-181a 32 , miR-21 25, 26, 30 and miR-155 30 with worse disease free-survival.…”
Section: Resultsmentioning
confidence: 99%
“…Among these it can be distinguished that the levels of 37 C-miRNAs have been found to be up-regulated (Table 4) while the levels of nine miRNAs were found to be down-regulated (Table 4). Another group of two C-miRNAs were found to be disregulated (Table 4), and can be used in the future to define a signature of tumor presence and stage [156].…”
Section: Gastrointestinal Oncologymentioning
confidence: 99%